2021
DOI: 10.1186/s12955-021-01843-4
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in a general population sample in Kazakhstan and its sociodemographic and occupational determinants

Abstract: Background Health-related quality of life (HRQL) in the general population of Kazakhstan has never been characterized. We constructed this population-based study of the largest city in Kazakhstan, Almaty with the aim to quantitatively assess HRQL and ascertain whether occupation and lifestyle are associated with HRQL in this population. Methods In a random sample (N = 1500) of general population in Almaty (median age 49 (interquartile range 28) yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Such high exposure to gaseous and particulate air pollution in Almaty has devastating effect on population health, including respiratory and cardiovascular effects. We earlier reported that physical component of health-related quality of life in Almaty was low [ 14 ], and its association with very poor air quality would likely be confirmed in future studies, yet unpublished. Respiratory and cardiovascular burden of extreme air pollution in Almaty has never been comprehensively assessed, but can allegedly be high, given that 15% of general population complains of clinically relevant respiratory symptoms and only 24% of subjects with verified chronic obstructive pulmonary disease (COPD) in the study were ever told they had COPD [ 15 ].…”
Section: Discussionmentioning
confidence: 78%
“…Such high exposure to gaseous and particulate air pollution in Almaty has devastating effect on population health, including respiratory and cardiovascular effects. We earlier reported that physical component of health-related quality of life in Almaty was low [ 14 ], and its association with very poor air quality would likely be confirmed in future studies, yet unpublished. Respiratory and cardiovascular burden of extreme air pollution in Almaty has never been comprehensively assessed, but can allegedly be high, given that 15% of general population complains of clinically relevant respiratory symptoms and only 24% of subjects with verified chronic obstructive pulmonary disease (COPD) in the study were ever told they had COPD [ 15 ].…”
Section: Discussionmentioning
confidence: 78%
“…Recent research based on Kazakhstan's general population's subjective perception of well-being found that low monthly income was one of the strongest negative predictors of poor physical and mental health [26]. In addition, considerable inequalities in selfrated health related to material deprivation were found in a Kazakhstani population of mature people aged 45+ [27].…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL is also an important predictor of survival [5], which means that HRQoL is important to measure and monitor. Decreased HRQoL is described as the result from suffering from health conditions and reflects individuals' adaptation to the adverse health outcomes of health conditions [6], wherefore understanding which factors that affect HrQoL is important for public health decisions. HRQoL is likely determined by the interplay of multiple physical, mental and socioeconomic factors, and this complex interplay must be accounted for in analyses to fully understand differences in HRQoL [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…HRQoL is likely determined by the interplay of multiple physical, mental and socioeconomic factors, and this complex interplay must be accounted for in analyses to fully understand differences in HRQoL [7,8]. In the middle age, the prevalence of diseases and troublesome symptoms starts to increase [6], which can significantly decrease HRQoL, and the factors explaining variance in HRQoL can be studied meaningfully. It is important to identify factors that can be modified in younger and middle-aged populations to be able to improve future health by public health policies and interventions during and, especially, before reaching an older age.…”
Section: Introductionmentioning
confidence: 99%